Mindfulness, Problem-solving Skills and Academic Achievement: Do Perceived Stress Levels Matter? - Dikmen, Melih (My University, 2022)
This study examines the relationship between higher education students’ perceived stress levels, and their problem solving skills, awareness levels and academic achievement. Also, the mediating role of mindfulness levels and problem-solving skills on the association between perceived stress level and academic achievement was investigated. The research was designed according to the correlational research design, one of the quantitative research methods. The participants of the study consisted of 938 higher education students. For data collection, three different questionnaires were administered to the participants. In addition, the personal information form prepared by the researcher was used to obtain the students’ demographic characteristics and grade point averages (GPA). The results showed that there was a significant negative relationship between perceived stress levels of higher education students and their mindfulness, problem solving skills, and academic achievement. Also, it was found that mindfulness and problem-solving skills had a mediating role in the association between perceived stress level and academic achievement. Based on the findings of the study, it was concluded that mindfulness-based approaches and problem-solving skills are important for higher education students to reduce their stress levels and increase academic success. The limitations and recommendations for future research are discussed.
Keywords: Stress; problem-solving skills; higher education students; academic achievement; mindfulness